Monetary Union Among Member Countries of the Gulf Cooperation Council - Fasano-Filho, Ugo (Occasional Papers; Occasional Paper ;, 2003)
The six member countries of the Gulf Cooperation Council (GCC)--Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates--have made important progress toward economic and financial integration, with the aim of establishing an economic and monetary union. This paper provides a detailed analysis of the economic performance and policies of the GCC countries during 1990-2002. Drawing on the lessons from the experience of selected currency and monetary unions in Africa, Europe, and the Caribbean, it assesses the potential costs and benefits of a common currency for GCC countries and also reviews the options for implementing a monetary union among these countries.